Diagnostic ability of confocal scanning ophthalmoscope for the detection of concurrent retinal disease in eyes with asteroid hyalosis. - Su Hwan Park; Ji Hyoung Chey; Jun Heo; Kwang Eon Han; Sung Who Park; Iksoo Byon; Han Jo Kwon (PLoS ONE)
Purpose To compare the diagnostic capacity of a color fundus camera (CFC), ultra-wide-field bicolor confocal scanning laser ophthalmoscope (BC-cSLO; OPTOS), and true-color confocal scanning ophthalmoscope (TC-cSO; EIDON) in detecting coexisting retinal diseases in eyes with asteroid hyalosis (AH). Methods The medical records of consecutive patients with AH who were referred to a tertiary hospital for subsequent assessment by a vitreoretinal specialist were retrospectively reviewed. Fundus images obtained simultaneously using CFC, BC-cSLO, and TC-cSO were classified into four grades based on their obscuration by asteroid bodies. The proportion of Grade 1 images (minimal obscuration group) was assessed for each imaging modality. The diagnostic and screening abilities for concurrent retinal diseases were compared in terms of the accuracy and sensitivity of each device. Results Among the 100 eyes with AH, 76 had coexisting retinal diseases, such as diabetic retinopathy (DR), retinal vascular occlusion, age-related macular degeneration, epiretinal membrane, and retinitis pigmentosa. TC-cSO had the highest ratio of Grade 1 images (94%, P<0.001), followed by CFC (67%) and BC-cSLO (63%). CFC and BC-cSLO exhibited a 5.3-fold higher rate of significant obscuration than TC-cSO (P<0.001, 95% confidence intervals = 2.4~11.6 folds). TC-cSO demonstrated the highest accuracy and sensitivity (95% and 81%, respectively) compared with CFC (89% and 43%, respectively) and BC-cSLO (89% and 39%, respectively) for all retinal diseases. BC-cSLO showed the best performance for DR diagnosis. Conclusions TC-cSO images showed minimal obscuration and a superior ability for diagnosing retinal diseases accompanied by AH over other imaging devices. TC-cSO can be a valuable alternative screening tool for detecting retinal diseases when AH impedes fundus imaging.